UPAYA GURU FIQH DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI MTs BAROKATUL QODIRI PENGUBUAN LAMPUNG TENGAH - Ani Rohayati; Andi Warisno; Nur Hidayah; Etika Pujianti (UNISAN JURNAL, 2023)
The purpose of this study was to find out the teacher’s efforts to increase learning motivation at MTs Barokatul Qodiri. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographic location in the form of a location plan and environmental conditions, the school’s vision, mission, strategy and motto as well as the condition of human resources at MTs Barokatul Qodiri. The fiqh teacher at MTs Barokatul Qodiri has made various efforts by the fiqh teacher in motivating students to learn in Fiqh subjects such as: being professional in teaching, implementing reading activities from a variety of reading sources, fostering social situations in the classroom, managing and shaping places and rooms conducive learning, being open to students, utilizing varied learning methods, raising challenges, conducting evaluations, and paying attention to and understanding the differences in the characteristics of students between one another. However, these efforts are reviewed from a performance perspective and the realization has not been fully successful.